Estabilização postural do olhar: efeitos da distância do objeto - Rodrigues, Sergio Tosi [UNESP]; Jardim, Juliana Gomes [UNESP]; Siqueira, Natalia Silva [UNESP]; Zago, Paula Fávaro Polastri [UNESP]; Aguiar, Stefane Aline [UNESP] (My University, 2011)
The aim of the present study was to analyze the effects of looking at targets located at different distances on body oscillation during tasks of distinct difficulties. In Experiment 1, ten participants in quiet stance fixated targets in three conditions: No object-far (fixation on far-target without near-target), Object-near (fixation on near target with fartarget), and Object-far (fixation on far-target with near-target). Mean oscillations of trunk in anterior-posterior axis were smallest in the Object-near condition; the No object-far and Object-far conditions were similar. In Experiment 2, seven participants in kiba-dachi, a karate stance, were submitted to three conditions: Blindfolded, No object-far, and Object-near. Mean oscillations of head and trunk in anterior-posterior axis were smaller in the Object-near as compared to blindfolded condition; trunk oscillated more during No object-far than Object-near condition. The results support the notion that a simple posture is not automatically regulated by the optical flow, but different amounts of visual instability may be tolerated according to the fixation distance, regardless the presence of non-fixated objects; the control of a more difficult posture may also accommodate the effects of fixation distance.
Keywords: Postural control; Stabilization of looking; Visual information; Suprapostural task